2019
DOI: 10.29313/mimbar.v35i2.5022
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Electronic Government in the Citizen-Centric Approach in Bandung City

Abstract: This paper aims to exploit e-government effectiveness from the perspective of users by focusing on online-based business licensing services in Bandung City. This paper also aims to develop the E-government Citizen Satisfaction Framework proposed by Sigwejo and Pather (2016). The method used is a qualitative method in e-government research. The results show that there is a gap between the services provided and community expectations. Online-based business licensing services in Bandung City have not been fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Institutions in organizations and work units are formed optimal if there is no support from top management (Erhan et al, 2017). The importance of institutions that are supported by top management is expected to give birth to simple service procedures and good coordination between agencies (Susanti et al, 2019).…”
Section: 32institutionalmentioning
confidence: 99%
See 2 more Smart Citations
“…Institutions in organizations and work units are formed optimal if there is no support from top management (Erhan et al, 2017). The importance of institutions that are supported by top management is expected to give birth to simple service procedures and good coordination between agencies (Susanti et al, 2019).…”
Section: 32institutionalmentioning
confidence: 99%
“…As it was found that there were inactive applications, the application was not optimal because it was only information and less integrated with services (V. N. F. Putri & Priyadi, 2018), as well as online services on website-based e-Government (Setyadi, 2019;Widiyarta et al, 2020). Another obstacle is related to less-than-optimal integration and interoperability, with incomplete and less detailed content (Bouty et al, 2019;Jatmiko & Astuti, 2018;Susanti et al, 2019).…”
Section: 33applicationmentioning
confidence: 99%
See 1 more Smart Citation